A little bit of knowledge: Facebook's News Feed and self-perceptions of knowledge. (January 2019) - Anspach, Nicolas M.; Jennings, Jay T.; Arceneaux, Kevin
Given that approximately half of Internet users use Facebook to access news, it is no surprise that social media are increasingly seen as a viable source of political information. Despite the fact that the average social media user only clicks on a small fraction of political content available in their News Feed, social media use correlates with political knowledge. From where, then, does this knowledge come? We argue that Facebook's News Feed itself, with its short article previews, provides enough political information for learning to occur. However, this learning comes with an additional consequence: audiences who only read article previews think they know more than they actually do, especially individuals who are motivated to seek emotions. While we are agnostic to the normative implications of such overconfidence, it is worth noting that similar behaviors are associated with political efficacy, knowledge, and participation.